Coastal erosion and coastal defense interventions: a cost-benefit analysis - Roebeling, P. C. (2020)
Coastal zones experience increased rates of erosion due to natural and anthropogenic causes. Although impacts from erosion are confined to coastal zones, these areas host over 40% of world population and a variety of ecosystems. Hence, these ecosystems and associated values may be lost due to coastal erosion. Establishment of coastal protection interventions can mitigate erosion, though their effectiveness is location-specific while implying large investment and maintenance costs. Coastal zone managers should, therefore, rely on cost-benefit analyses when defining coastal management strategies – to date these strategies are defined on the basis of physical- and cost-effectiveness studies, while cost-benefit analyses have only been applied at regional and global scales. We develop and apply a spatially-explicit approach that allows for the cost-benefit assessment of coastal protection investment options at the local scale, using the shoreline evolution model LTC (Long-Term Configuration) in combination with benefit transfer approaches for the valuation of coastal ecosystems. For the Central Portuguese case study, baseline results show that coastal erosion leads to area losses of ~850 ha by 2050. Scenario simulations show that all assessed interventions reduce though not halt territory losses. Cost-benefit analysis shows, however, that construction of new groins is not attractive while artificial nourishments, extension of existing groins and construction of longitudinal revetments provide positive returns to investment. Hence, even when coastal erosion will occur sooner or later in time, it may be worthwhile to protect coastal areas as benefits obtained from not (yet) eroded areas may outweigh costs foregone through their (temporary) protection.